A wideband dielectric resonator antenna with a cross slot aperture for 5G communications - Abinash Gaya; Mohd Haizal Jamaluddin; M. R. Kamarudin; Irfan Ali (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2019)
This paper represents design of a wideband Rectangular Dielectric Resonator antenna fed by an aperture coupled technique. A bandwidth of 2.2 GHz has been achieved using a cross slot aperture in a ground plane for Dielectric Resonator Antenna (DRA). The simulated gain value achieved is 6.5dBi. The Rectangular Dielectric Resonator which has been designed in this paper can be used in 5G application frequency band of 24.25-27.5 GHz. The calculated percentage bandwidth is 15.38 %. An optimization of slot dimensions has also mentioned which can help to select a desired impedance match. The measured gain and bandwidth are efficient to use this design for various 5G applications. This unit cell wideband DRA can be used for millimeter wave frequencies of 5G.